The discourse of enclosure : representing women in Old English literature - Horner, Shari, 1961- (Albany : State University of New York Press, 2001)
"Exploring Old English texts ranging from Beowulf to Aelfric's Lives of Saints, this book examines ways that women's monastic, material, and devotional practices in Anglo-Saxon England shaped literary representations of women and femininity. Horner argues that these representations derive from a "discourse" of female monastic enclosure, based on the increasingly strict rules of cloistered confinement that regulated the female religious body in the early Middle Ages. She shows that the female subjects of much Old English literature are enclosed by many layers - literal and figurative, textual, material, discursive, and spatial - all of which image and reinforce the powerful institutions imposed by the Church on the female body. Though it has long been recognized that medieval religious women were enclosed, and that virginity was highly valued, this book is the first to consider the interrelationships of these two positions - that is, how the material practices of female monasticism inform the textual operations of Old English literature."--Jacket
Introduction The Discourse of Enclosure: Inscribing the Feminine in Old English Literature 1 -- Chapter 1 Looking Into Enclosure in the Old English Female Lyrics 29 -- Chapter 2 Voices From the Margins: Women and Textual Enclosure in Beowulf 65 -- Chapter 3 Textual/Sexual Violence: The Old English Juliana and the Anglo-Saxon Female Reader 101 -- Chapter 4 Bodies and Borders: The Hermeneutics of Enclosure in Elfric's Lives of Female Saints 131 -- Conclusion Christina of Markyate and Legacies of Enclosure 173.
Includes bibliographical references (pages 187-202) and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: English literature -- Old English, ca. 450-1100 -- History and criticism; Women and literature -- England -- History -- To 1500.; Feminism and literature -- England -- History -- To 1500.; Women -- England -- History -- Middle Ages, 500-1500.; Enclosure (Monasticism) -- History -- To 1500.; Women in literature; Littérature anglaise -- ca 450-1100 (Vieil anglais) -- Histoire et critique; Femmes et littérature -- Angleterre -- Histoire -- Jusqu'à 1500.; Féminisme et littérature -- Angleterre -- Histoire -- Jusqu'à 1500.; Femmes -- Angleterre -- Histoire -- 500-1500 (Moyen Âge); Clôture (Monachisme) -- Angleterre -- Histoire -- Jusqu'à 1500.; Femmes dans la littérature.; LITERARY CRITICISM -- European -- English, Irish, Scottish, Welsh; Enclosure (Monasticism); English literature -- Old English; Feminism and literature; Women and literature; Women in literature; Women -- Middle Ages; England; Altenglisch; Literatur; Geschichte; Frau; Altenglisch; To 1500; Criticism, interpretation, etc; History